We need to perform the product of:
![-4x^3y^2\text{ }\cdot(6x^3y^6)](https://img.qammunity.org/2023/formulas/mathematics/college/veupfu6m2ljh9cjvym6y28x7i254jlo1ty.png)
So we start by multiplying the numerical factors first:
(-4) times 6 = -24
This is then the value we enter for A = -24
Now for the product of the variables x:
one has the power "3" and the other one has the power 3 as well, so the new expression in power (exponent) form for x is x to the power "3+3 = 6"
![x^6](https://img.qammunity.org/2023/formulas/mathematics/high-school/oidvlvujbyiyhjvhffiidjt1xt482x4mca.png)
Noe for the powers of the variable y:
we have to multiply y to the second power 92) times y to the sixth power (6), which leads to y to the "2 + 6 = 8" power, that is:
![y^8](https://img.qammunity.org/2023/formulas/mathematics/college/4x52cnl9y5jsqbz083rqyzmxnnb2z09115.png)
So now we write:
A = -24, m = 6 , and n = 8